Examination of breath alcohol concentration (BrAC) levels, alcohol use disorders identification test (AUDIT‐C) classification, and intended plans for getting home among bar‐attending college students. (30th March 2015) - Martin, Ryan J.; Chaney, Beth H.; Cremeens‐Matthews, Jennifer
<x xml:space="preserve">Abstract</x> Background and Objective The college student population is one of the heaviest drinking demographic groups in the US and impaired driving is a serious alcohol‐related problem. The objective of this study is to better understand the relationship between alcohol‐related behaviors and "plans to get home" among a sample of college students. Methods We conducted four anonymous field studies to examine associations between breath alcohol concentration (BrAC) levels, Alcohol Use Disorders Identification Test (AUDIT‐C) classification, and plans for getting home among a sample of bar‐attending college students (N = 713). Results, Discussion and Conclusions The vast majority of participants in our sample (approximately 95%) were not intending to drive and the average BrAC% of those intending to drive was .041. Our one‐way ANOVAs indicated that (1) participants classified by the AUDIT‐C as not having an alcohol problem had a significantly lower BrAC% than those classified as having a potential problem and (2) participants planning to drive had a significantly lower BrAC% than those with a plan that did not involve them driving and those without a plan to get home. Although it is encouraging that most of our sample was not intending to drive, it is important to continue to attempt to reduce impaired driving in this population. Scientific Significance This study helps college health professionals and administrators to better understand the relationship between alcohol‐related behaviors and plans to get home among college students. (Am J Addict 2015;XX:XX –XX)